Longitudinal growth of the Saccharina kelp embryo depends on actin filaments that control the formation of a corset-like structure composed of alginate - Samuel Boscq; Ioannis Theodorou; Roman Milstein; Aude Le Bail; Sabine Chenivesse; Bernard Billoud; Bénédicte Charrier (Scientific Reports)
Abstract The initiation of embryogenesis in the kelp Saccharina latissima is accompanied by significant anisotropy in cell shape. Using monoclonal antibodies, we show that this anisotropy coincides with a spatio-temporal pattern of accumulation of alginates in the cell wall of the zygote and embryo. Alginates rich in guluronates as well as sulphated fucans show a homogeneous distribution in the embryo throughout Phase I of embryogenesis, but mannuronate alginates accumulate mainly on the sides of the zygote and embryo, disappearing as the embryo enlarges at the start of Phase II. This pattern depends on the presence of cortical actin filaments. In contrast, within the embryo lamina, the alginate composition of the walls newly formed by cytokinesis is not affected by the depolymerisation of actin filaments. Thus, in addition to revealing the existence of a mannuronate-rich alginate corset-like structure that may restrict the enlargement of the zygote and the embryo, thereby promoting the formation of the apico-basal growth axis, we demonstrate stage- and cytoskeleton-dependent differences in cell wall deposition in Saccharina embryos.